Letter to the editor: radiomics analysis for predicting pembrolizumab response in patients with advanced rare cancers. Issue 7 (27th July 2021) - Cunha, Mateus Trinconi; Carvalho, Vinicius Jardim; Loureiro, Rafael Maffei; Brantis-de-Carvalho, Carlos Eduardo; Cintra, Murilo Bicudo; de Castro Junior, Gilberto
Abstract : A commentary on the original research article: 'Radiomics analysis for predicting pembrolizumab response in patients with advanced rare cancers'. Of note, the predictor selection process, the cross-validation method, along with the lack of final testing of the developed model with a separated data set may mask overfitting, overestimating performance metrics.